Research progress in ZnO single-crystal: growth, scientific understanding, and device applications - Huang, Feng; Lin, Zhang; Lin, Wenwen; Zhang, Jiye; Ding, Kai; Wang, Yonghao; Zheng, Qinghong; Zhan, Zhibing; Yan, Fengbo; Chen, Dagui; Lv, Peiwen; Wang, Xian (Chinese science bulletin, 2014)
Zinc oxide, a wide band-gap semiconductor, has shown extensive potential applications in high-efficiency semiconductor photoelectronic devices, semiconductor photocatalysis, and diluted magnetic semiconductors. Due to the undisputed lattice integrity, ZnO single crystals are essential for the fabrication of high-quality ZnO-based photoelectronic devices, and also believed to be ideal research subjects for understanding the underlying mechanisms of semiconductor photocatalysis and diluted magnetic semiconductors. This review, which is organized in two main parts, introduces the recent progress in growth, basic characterization, and device development of ZnO single crystals, and some related works in our group. The first part begins from the growth of ZnO single crystal, and summarizes the fundamental and applied investigations based on ZnO single crystals. These works are composed of the fabrication of homoepitaxial ZnO-based photoelectronic devices, the research on the photocatalysis mechanism, and dilute magnetic mechanism. The second part describes the fabrication of highly thermostable n-type ZnO with high mobility and high electron concentration through intentional doping. More importantly, in this part, a conceptual approach for fabricating highly thermostable p-type ZnO materials with high mobility through an integrated three-step treatment is proposed on the basis of the preliminary research.